A Performance for Dinner: Dining Culture and Colonial Identity in the Dutch East Indies, 1880-1910 - Ørum, Emilie Bolding (Culture and History: Student Research Papers, 2024)
When photography arrived in the Dutch East Indies in the middle of the 19th century, European colonists embraced the medium to immortalise impressions of colonial life. By studying photographs produced by European colonists in the Dutch East Indies, this article examines dining culture as an arena of colonist regulation, construction and maintenance of colonist identity through visual and material performances and practices from approximately 1880 to 1920. The article argues that colonists upheld clear cultural and social separation from the colonised through dining practices which highlighted the European material culture around the dining table and gentile sensibilities modeled after the ideals of Victorian gentility in the colonial metropole. The complete social segregation and rejection of cultural assimilation that is evident in the examined photographs, served to maintain colonists’ European identity and exclusive positions of power in colonial society. The medium of photography enabled colonists to perpetuate, reinforce, and preserve the captured messages of colonist idealized life and superiority, as the photographs were continually shared in both private and public European spheres.